Student self-assessment of oral explanations: Use of language learning progressions. (July 2019) - Goral, Despina P.; Bailey, Alison L.
Students' self-assessment of language features in their oral explanations of a mathematics task was supported by language learning progressions. Learning progressions map a continuum of knowledge or skills development as they increase in sophistication over time. Learning progressions can be a framework to support formative assessment by both teachers and students. Fifty-eight predominantly English-speaking US elementary students used language learning progressions to complete their self-assessment of either discourse stamina or vocabulary usage in the elicited oral explanations. Students were guided through a four-step, highly scaffolded self-assessment protocol that was analyzed for (1) concordance with researcher placements of their explanations on the progressions, and (2) student commentary on their own placements. Overall, 50% of the students self-assessed in accordance with researchers' independent placement of their explanations on the progressions. However, significant grade-level and gender differences in concordance were found. Results were consistent with prior research findings that upper-elementary students' self-assessments are more aligned with external measures than are younger students' self-assessments (e.g., Butler & Lee, 2006). However, even the youngest students in the current study were able to complete the self-assessment activity, if not always with the same degree of concordance. Successful participation may be attributable to the format, scaffolding, and contextualization of the self-assessment activity with its use of language learning progressions. Also consistent with prior research, girls were more likely to agree with researchers' placements than boys. Student self-assessment differed by the two language features. Most students found the self-assessment activity to be a useful learning experience. Implications for research and practice are discussed.